Systems information modeling: From file exchanges to model sharing for electrical instrumentation and control systems - Love, P.; Zhou, Jingyang; Matthews, J. (Elsevier BV, 2016)
Crown Copyright © 2016 Published by Elsevier B.V. All rights reserved. The mining industry in Australia is in a period of intense introspection as it seeks to improve its productivity and competitiveness in global markets. With mining projects experiencing increasing overruns on capital expenditure, there is a need to re-examine existing business practices to address the prevailing productivity crisis that the industry is experiencing. In addressing this issue, within the context of electrical instrumentation and control systems (EICS), a case study that examines the development of a systems information model (SIM) to improve productivity during the engineering, construction, maintenance, and operations processes of a magnetite iron ore processing plant is presented and discussed. By transforming the established document oriented information exchanges that are typically used in EICS projects to a more collaborative data-sharing environment, processes were streamlined and errors, as a result of duplication and inconsistency, were significantly prevented from occurring. While still working within the restriction of discipline-specific models, the creation of a SIM is the first step towards an integrated and interoperable data without a reliance on drawings.